Efektifitas Edukasi Budaya Keselamatan Terhadap Penerapan Keselamatan Pasien - Dangan Panggalih (Jenggala : Jurnal Riset Pengembangan dan Pelayanan Kesehatan, 2023)
Patient safety efforts to reduce the number of adverse events in hospitals, namely by implementing the seven steps of hospital patient safety. The aim of the study was to analyze the effectiveness of safety culture education on patient safety implementation. This systematic review began with a literature review from various sources. Articles were collected using search engines such as PubMed, google schoolar, science direct, ProQuest and Elsevier. The articles used in the study were published from 2012-2023. Articles were searched using keywords that have been determined by the researcher then articles were extracted based on inclusion and exclusion criteria using the PRISMA protocol. Thus, 7 articles were found that matched the critical appraisal criteria for analysis. Based on the collected articles, it was found that. Safety culture is the first cause of problems in implementing patient safety goals. Safety culture is a highly specialized and meaningful process for nurses in the process of implementing patient safety goals in hospitals. An effective safety culture that is timely, accurate, complete, clear, and understood by recipients reduces errors and improves patient safety. The conclusion of the study is that health services that prioritize patient safety require an optimal role for nursing in this case a safety culture. The implementation of a safety culture in implementing patient safety goals is very complex and can be influenced by many factors.